Marketing strategy and management - Baker, Michael John. (Baskingstoke, Hampshire ; New York : Palgrave Macmillan, 2007)
'Marketing Strategy and Management' retains the traditional functional approach to marketing but incorporates research and topical examples and cases to encourage students to apply theoretical principles and frameworks to practical real-world situations.
Includes bibliographical references and index.
Keywords: Marketing -- Management; Marketing